2021
DOI: 10.7759/cureus.16199
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Use of Incentives and Penalties for Point-of-Care Ultrasound Documentation Compliance in an Academic Emergency Department

Abstract: Incomplete documentation and submission to the electronic health record of performed point-of-care ultrasound (POCUS) studies is problematic from a patient care, medicolegal, and billing standpoint. Positive and negative financial incentives may be used to motivate physicians to complete documentation workflow. The most efficacious route to improve POCUS workflow completion remains to be determined. Materials and methodsA retrospective analysis of POCUS documentation in an academic emergency department during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…We also believe the department leadership's willingness to offer a financial incentive made a profound statement as to the importance of achieving this training as well as recognizing that practicing physicians should have some compensation as to the amount of time needed to achieve privileging. The positive impact of financial incentive on POCUS training and documentation is consistent with prior reports 27,28 . Similar to our model, Budhram et al 27 built in a financial incentive into their POCUS training and privileging program from the beginning.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We also believe the department leadership's willingness to offer a financial incentive made a profound statement as to the importance of achieving this training as well as recognizing that practicing physicians should have some compensation as to the amount of time needed to achieve privileging. The positive impact of financial incentive on POCUS training and documentation is consistent with prior reports 27,28 . Similar to our model, Budhram et al 27 built in a financial incentive into their POCUS training and privileging program from the beginning.…”
Section: Discussionsupporting
confidence: 88%
“…While they did not directly measure the effect that this financial incentive played, they theorized that the incentive as well as deadlines were a key part of successfully privileging a small cohort of EPs. Similarly, Melton et al 28 found that providing both positive and negative financial incentives resulted in improved POCUS documentation among EPs who had already achieved POCUS privileges, ultimately improving the rate and number of POCUS studies that were completed for clinical care. While a financial incentive seems to be a reliable motivator for POCUS education and credentialing, there are examples of successful educational programs without a financial component.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[1][2][3] Despite the necessity and ubiquity of ED POCUS, many centers have described a lack of consistency and accuracy in documentation. [4][5][6] Commonly cited reasons for poor POCUS documentation often include lack of time on shift and the need for manual patient data entry into the ultrasound machines. Physicians report that ultrasound documentation processes are too time intensive and require logging onto multiple electronic health records (EHRs) and picture archive and communications systems (PACS).…”
Section: Introductionmentioning
confidence: 99%